Co-Operation Model in Gem and Jewelry Industrial Development in ASEAN Group of Countries A Case Study of Thai-Cambodia - Rintanalert, Chananun; Srison, Wichitra; Chayayanon, Sunthan (Journal of Humanities and Social Sciences Thonburi University, 2021)
The objective of this research is the current state, elements of cooperation and to find a model for cooperation in the development of gems and jewelry industry in ASEAN, Thailand-Cambodia. We used questionnaires and interview to collect both quantitative and qualitative data, the sample group consisted of gem and jewelry business entrepreneurs. The affirmative factor then prepped to analyze data from questionnaires and content-oriented information to analyze data from interviews. The research results are shown as follows: Current conditions is components involved: structure and cooperation mechanism, resources to support cooperation, cooperation process, and main aspects of cooperation The cooperative variables: measures to help government, cooperation between states, promoting product quality, packaging, brand building, after analyzing confirmed following factors, found that there were only three components left: government assistance measures, cooperation between states and promoting product quality, packaging, brand building and cooperation model for the development of gem and jewelry industry in ASEAN, Thailand-Cambodia influenced: structure and cooperation mechanism, resources to support process, and main aspects of cooperation.